Strategy in manipulating transglycosylation activity of glycosyl hydrolase for oligosaccharide production - Nor Hasmaliana, Abdul Manas; Rosli, Md. Illias; Nor Muhammad, Mahadi (Taylor and Francis Ltd, 2018)
Background: The increasing market demand for oligosaccharides has intensified the need for efficient biocatalysts. Glycosyl hydrolases (GHs) are still gaining popularity as biocatalyst for oligosaccharides synthesis owing to its simple reaction and high selectivity. Purpose: Over the years, research has advanced mainly directing to one goal; to reduce hydrolysis activity of GHs for increased transglycosylation activity in achieving high production of oligosaccharides. Design and methods: This review concisely presents the strategies to increase transglycosylation activity of GHs for oligosaccharides synthesis, focusing on controlling the reaction equilibrium, and protein engineering. Various modifications of the subsites of GHs have been demonstrated to significantly modulate the hydrolysis and transglycosylation activity of the enzymes. The clear insight of the roles of each amino acid in these sites provides a platform for designing an enzyme that could synthesize a specific oligosaccharide product. Conclusions: The key strategies presented here are important for future improvement of GHs as a biocatalyst for oligosaccharide synthesis. © 2017 Informa UK Limited, trading as Taylor & Francis Group.